HUKUM ISLAM PADA PERIODE IMAM MAZHAB - Ali Akbar; Nurul Hafizha Rokan; Niza Alfira; Lily Dahreni Siregar; Aldi Saputra Siregar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This article discusses the history of Islamic legal thought among the tabi'in. The development of Islamic law during the Tabi'in era was known to be marked by the emergence of political tendencies which implicitly encouraged the establishment of legal schools. The formation of this sect indirectly proves that Islam has freedom of thought and each sect is free to tolerate each other or respect existing differences. This difference means that there are no obstacles to coexistence or Muslim brotherhood. In general, the term tabi'in follows in the footsteps of the Friends of Istinbath Al Ahkam who established and implemented the law. This legal istinbath is achieved through ijtihad according to the rules of Islamic sources, such as the Al-Qur'an, Sunnah, contract, and qiyas. The emergence of this school occurred in those years. Because of advances in science. So this period is considered the golden period in the development of Islamic law. The main factor is the development of Islamic law along with the progress of science in the Islamic world. Thus, this school of fiqh emerged after his fellow followers wrote down their 13 schools of thought. There are 13 registered mujtahid schools, 13 of which are mujtahid schools, and their opinions are all related to the Al Sunnah School. However, there are only four famous schools of thought: Imam Hanafi, Imam Malik, Imam Syafi'i, and Imam Hanbali.